(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Physical inactivity is a serious public health issue that impacts a large number of people worldwide, according to the WHO. One of the main underlying causes of illness, mortality, and disability is a sedentary lifestyle. The level of life has risen in developing nations due to industrialisation and urbanisation. Obesity has become more common as a result of sedentary lifestyles and improper eating habits. One of the main causes of disorders like hypertension, sleep apnoea, diabetes mellitus, coronary heart disease, stroke, osteoarthritis, and dyslipidaemia, obesity can have a major negative impact on one’s physical and emotional well-being and increase morbidity and mortality.Furthermore, these circumstances may have severe social and economic repercussions, particularly in developing and poor nations (WHO, 2008).